Food fights: irritating for social change among Auckland's alternative food initiatives. (2nd July 2016) - Sharp, EL; Schindler, E; Lewis, N; Friesen, W
ABSTRACT: This article explores alternative food initiatives (AFI) and their performances of benign transgression. Through collaborative activist-and-academic-storytelling we tease apart the divergent practices of AFIs to question what mediates these performances in the grey area between conventional and alternative practice. Grounded examples of AFIs performing alternative economy and related acts of 'irritant' civil disobedience show how subverting normative practices of power and authority can catalyse social reproduction of difference, and tangibly alter the conventional food system.